Back Cover: Biotechnology Journal 3/2019. Issue 3 (1st March 2019) - Unknown
Abstract : Data management and kinetic modelling of biocatalytic data is integrated into a workflow. Experimental data on reaction conditions and the time courses of substrate and product concentrations are uploaded into the BioCatNet database system. Model selection and parameter estimation is performed by simultaneously fitting different macro‐ and microkinetic models to the ensemble of progress curves. This is reported by Patrick C. F. Buchholz, Rüdiger Ohs, Antje C. Spiess, and Jürgen Pleiss in article1800183 .